2015
DOI: 10.17795/zjrms1011
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect of Aqueous, Ethanol, Methanol and Glycerin Extracts of Satureja bachtiarica on Streptococcus pyogenes, Pseudomonas aeruginosa and Staphylococcus epidermidis

Abstract: Background:The Iranian medicinal plants, such as Satureja bachtiarica have been utilized as traditional medicines by the indigenous people of Chaharmahal and Bakhtiari in Iran. Objectives: According to biologically active compounds and traditional use of the Satureja bachtiarica, seem that this plant has significant antimicrobial effects. Materials and Methods: In this experimental study, Satureja bachtiarica after extraction with watery, ethanol 96%, methanol 96% and 20% glycerin antimicrobial effect of extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Heidari Sureshjani et al (2013) also reported higher inhibitory and bactericidal activities for ethanol extract of Satureja than those of the water extract. They attributed these findings to the dry weight of the extract [12].…”
Section: Extract Typementioning
confidence: 95%
See 3 more Smart Citations
“…Heidari Sureshjani et al (2013) also reported higher inhibitory and bactericidal activities for ethanol extract of Satureja than those of the water extract. They attributed these findings to the dry weight of the extract [12].…”
Section: Extract Typementioning
confidence: 95%
“…They reported that the antimicrobial effect increased as the concentrations increased because the antimicrobial compounds increased [12]. It has been shown in several studies that different concentrations of the extract influence the increment of antimicrobial effect.…”
Section: Extract Concentrationmentioning
confidence: 98%
See 2 more Smart Citations
“…Aromatic plants, known for both aromatic and antiseptic properties, are used in spices and natural food preservatives, perfume industry for aromatherapy, etc. (2,3). During the last decades, natural products with antimicrobial effect have been investigated for eliminating the use of synthetic antibiotics that cause the resistance of microorganisms and have side effects to human health (4).…”
Section: Introductionmentioning
confidence: 99%